2017
DOI: 10.1007/s00449-017-1806-y
|View full text |Cite
|
Sign up to set email alerts
|

Cauliflower waste utilization for sustainable biobutanol production: revelation of drying kinetics and bioprocess development

Abstract: Efficient yet economic production of biofuel(s) using varied second-generation feedstock needs to be explored in the current scenario to cope up with global fuel demand. Hence, the present study was performed to reveal the use of cauliflower waste for acetone-butanol-ethanol (ABE) production using Clostridium acetobutylicum NRRL B 527. The proximate analysis of cauliflower waste demonstrated to comprise 17.32% cellulose, 9.12% hemicellulose, and 5.94% lignin. Drying of cauliflower waste was carried out in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Although other authors have reported the possibility of using cauliflower residues from various points of view [ 14 , 15 ], this is the first work where their beneficial properties have been studied in order to be improved with regard to the pharmaceutical, cosmetics, and food industries. It is known that thermal stress is accompanied by an increase in the concentration of reactive oxygen species [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although other authors have reported the possibility of using cauliflower residues from various points of view [ 14 , 15 ], this is the first work where their beneficial properties have been studied in order to be improved with regard to the pharmaceutical, cosmetics, and food industries. It is known that thermal stress is accompanied by an increase in the concentration of reactive oxygen species [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some previous works have attributed such high antioxidant activity not only to phenolic compounds, but also to substances such as soluble fiber, glucosinolates, and their derived products, such as isothiocyanates, that are present in cauliflower waste and have potent anticancer effects [15]. Although other authors have reported the possibility of using cauliflower residues from various points of view [14,15], this is the first work where their beneficial properties have been studied in order to be improved with regard to the pharmaceutical, cosmetics, and food industries. It is known that thermal stress is accompanied by an increase in the concentration of reactive oxygen species [4].…”
Section: Evaluation Of the Antioxidant Activity And Total Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Great amounts of cabbage wastes are dumped directly on the ground, leading to a serious threat to the environment. Moreover, their incineration plays a significant part in the increase of CO 2 levels [ 127 ]. Besides, bioethanol production, powder waste obtained from cauliflower was used from heavy metals removals such as Pb(II) and Cd(II) from synthetic solutions—the process is described with Langmuir and pseudo-second kinetic models [ 118 ].…”
Section: Types Of Pollutantsmentioning
confidence: 99%
“…Biowaste, in the form of vegetable or fruit waste, has become a major environmental concern due to its improper disposal. Among vegetables, India ranks second worldwide in cauliflower production, accounting for approximately 35% of total worldwide production [33]. Cauliflower (Brassica oleracea var.…”
Section: Introductionmentioning
confidence: 99%